Psychological Factors Of Motivation And Self-Regulation In Students’ Independent Learning Activities (Zien Journal of Social Sciences and Humanities, 2026)
This article examines the psychological factors of motivation and self-regulation in students’ independent learning activities. In modern education, independent learning plays a crucial role in the development of professional competencies and lifelong learning skills. The study analyzes intrinsic and extrinsic motivation as well as the key components of self-regulation, including goal setting, planning, monitoring, and reflection. The findings indicate that students’ success in independent learning largely depends on their ability to manage time effectively, apply appropriate learning strategies, and maintain selfcontrol. Empirical results show that students with higher levels of intrinsic motivation demonstrate greater engagement and productivity in their learning process. Furthermore, well-developed self-regulation skills contribute to deeper knowledge acquisition and sustained learning motivation. The study highlights the importance of integrating psychological support mechanisms into educational practices to enhance the effectiveness of independent learning in higher education.